The effect of a combined compression-tactile stimulating sock on postural stability - Marchant, Ashleigh; Wallwork, Sarah B.; Witchalls, Jeremy; Ball, Nick; Waddington, Gordon (Frontiers in Sports and Active Living, 2024)
Previous research has demonstrated that postural stability may be improved by increasing stimulation to the somatosensory system. Wearing lower limb compression garments or textured in-soles have been found to be effective short-term methods for improving postural stability, hypothesized to be due to enhanced tactile feedback. The aim of this study was to assess whether a combined compression-tactile sock increases postural stability in healthy adults, compared to barefoot. Participants completed a sensory organization test (SOT) to assess postural stability under two conditions: (a) barefoot, and (b) wearing a compression sock with a textured inner lining (small rubber nodules on the skin side of the sole). SOT composite scores and three sensory scores - somatosensory, vestibular, visual - were assessed between the two conditions to identify whether wearing the socks was associated with enhanced postural stability. Comparisons between the two conditions were analyzed via a paired t-test for the (i) entire group, and an ANOVA when the group was split into (ii) “high performers” and “low performers”, according to their baseline performance on the SOT. Fifty-four participants (28 females, 26 males, mean age 40 ± 14 years) completed the study. SOT scores were not different between the compression-tactile sock and barefoot conditions when analyzed as an entire group (p > 0.0125), or when the group was split into performance groups (p > 0.0125). These findings demonstrate that, for healthy adults, mixed compression and tactile stimulation socks do not appear to be associated with improved postural stability, when measured using the sensory organization test. Although prior research indicates that wearing a compression-tactile sock improves somatosensory acuity compared to being barefoot, these benefits do not seem to carry over to postural stability. It may be that in healthy adults, the additional sensory feedback becomes redundant, or the SOT is not challenging enough for this study population.